2763. Uptake and Safety of Measles-Mumps-Rubella (MMR) Vaccine in Adolescents and Adults in the Vaccine Safety Datalink - Hanson, Kayla E (Open Forum Infect Dis, 2019)
BACKGROUND: MMR vaccine is given routinely to young children but may be given at other ages. We described MMR use in adolescent and adult populations in the Vaccine Safety Datalink (VSD) and estimated the incidence of medically-attended outcomes after MMR to inform future studies estimating vaccine-associated risk. METHODS: The study population included adolescents (9–17 years) and adults (≥18 years) in VSD who received at least one MMR vaccine from 2010 through 2016. Outcomes were pre-specified based on previous vaccine safety studies and categorized as clinically serious (anaphylaxis, encephalitis/myelitis, GBS, meningitis, seizure) or non-serious (allergic reaction, arthropathy, fever, injection site reaction, lymphadenopathy, nonspecific reaction, parotitis, rash, syncope). Outcomes were identified by searching for ICD-9 and ICD-10 diagnosis codes in post-vaccination exposure windows. Medical records were reviewed for all serious outcomes to verify incident diagnoses. Incidence and 95% confidence intervals were calculated for validated serious and all non-serious outcomes. RESULTS: 146,503 adolescents and adults received 162,992 MMR vaccines during the study period. The mean age at vaccination was 33.7 years, 65% were female, and 53% received at least one other vaccine simultaneously. Demographic and vaccination characteristics varied across age groups (Table 1). The analysis of post-vaccination outcomes included 162,053 MMR vaccinations. The incidence of validated serious outcomes was low, ranging from 0 to 6.8 per 100,000 vaccinations. Only one serious outcome (anaphylaxis) was noted to be vaccine-associated in the medical record. Incidence of clinically non-serious outcomes varied from 0.4 to 56.0 per 10,000 vaccinations. Injection site reactions were more common among adolescents (118.1 per 10,000 vaccinations), who also had a higher frequency of simultaneous vaccination (80%). CONCLUSION: Clinically serious outcomes were rare following MMR vaccination. Rates of clinically non-serious outcomes varied but were similar to or lower than previous reports in children. This descriptive analysis did not evaluate the association between MMR and adverse events. Future analysis with an appropriate comparison group is needed for risk estimation. [Image: see text] DISCLOSURES: All authors: No reported disclosures.